PERAN INDONESIA TERHADAP ISU KESEHATAN GLOBAL MELALUI FORUM FOREIGN POLICY AND GLOBAL HEALTH (FPGH) DALAM GLOBAL HEALTH GOVERNANCE (GHG) 2006-2013 - Rizki Ari Kurniawan; Idjang Tjarsono, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains about the role of Indonesia to overcome the global health issue through Foreign Policy and Global Health (FPGH) forum, FPGH is formed by the foreign ministry of Indonesia, Norway, France, Thailand, Brazil, South Africa, and Senegal in order to emphasize the connection between foreign policy with the policy in health sector that nowadays becomes the international society interest.This research uses qualitative method with techniques of writing a literature review through library research from several sources like books, journals, articles, websites, the media and others.This research begins with explanning of the global health condition and what do Indonesia in addressing global health issues. To analyze the role of Indonesia to overcome this issue, this research uses two theories: Role Theory and Partnership Theory. The results showed that the Indonesian government will do anything to through the health ministry plays an active role in addressing global health issues.As the result, this research shows that Indonesia has the active role in overcoming the global health issue in order to increase the existence in the world. Indonesia‟s active role is especially showed in FPGH and World Health Assembly (WHA) council. The active role of Indonesia in overcoming the global health issue is significantly explained in the launching of Osco Declaration. Besides Indonesia also shows good leadership to foght for mechanism of Virus Sharing and Benefit Sharing justice for public health.Keywords: FPGH, World Health Assembly (WHA), Global Health, Sharing Viruses, Vaccines.